Retrospective of Open Access Repositories and Trends in the Socialization of Knowledge - Silvia Irene Adame Rodríguez; Luis Lloréns Baez; Michel Schorr Wiener (Universidad Autónoma de Baja California, 2013)
While searching for information on the Web is an everyday activity, finding free, reliable and quality information is a challenge, hence the interest in sharing part of a research project about repositories. The aim of this documentary research study is to present an overview of open access digital repositories and some trends in the socialization of knowledge produced by institutions of higher education, which in some way already mark a path toward a culture of sharing and reusing scientific, academic and cultural information for the benefit of the academic community and the general public.